Foliar calcium application reduces fluorine accumulation in tea plant by regulating cell wall structure and gene expression - Luo, Jinlei; Zhang, Lintao; Li, Daili; Huang, Shuangjie; Li, Chunlei; Chen, Yi; Yin, Peng; Liu, Wei; Sun, Mufang; Guo, Guiyi (Frontiers in Plant Science, 2025)
Tea plant can enrich a large amount of fluorine (F) in the cell wall of its mature leaves, thus posing the risk of excessive intake of F for tea consumers. This study investigated the effect of foliar calcium (Ca) application (0.05-1 mM) on F accumulation in tea plant leaves by analyzing the association of F with cell wall materials, pectin methylesterification structure, and cell wall genes. Ca spray could effectively reduce the F level, the content of wall carbohydrates (excluding the chelate pectin fraction) and the pectin methylesterification degree in tea plant leaves. Correlation analysis further revealed that the tea leaf F content was positively correlated with most of the cell wall materials. Transcriptomics analysis indicated that the key genes involved in reorganization of cell wall polysaccharides (such as CslE6, XTH32, PG, PGIP, PME18, PMEU1, and PMEI9) were associated with the variations in F content and cell wall components. All the results suggest that Ca may lessen the tea leaf F level by reducing the accumulation of cell wall materials and intervening the cell wall structure and gene expression. This study provided useful information for reducing the F level and solving the F safety problem in tea plant.